Effects of a mindfulness‐based intervention on mindfulness, stress, salivary alpha‐amylase and cortisol in everyday life. (15th September 2021) - Aguilar‐Raab, Corina; Stoffel, Martin; Hernández, Cristóbal; Rahn, Stefanie; Moessner, Markus; Steinhilber, Barbara; Ditzen, Beate
Abstract: A large body of literature has shown the effectiveness of mindfulness‐based interventions (MBI) on stress‐reduction. However, little is known about their effects on psychobiological stress‐markers in daily life through an ecological momentary assessment approach. Our study examines the effects of MBI on state mindfulness, perceived stress, and indicators of sympathetic‐nervous‐system (saliva alpha‐amylase, sAA) and hypothalamic‐pituitary‐adrenal‐axis (saliva cortisol, sCort) activation in daily life. Twenty‐eight individuals participated in a three‐month MBI (IG) and were compared to 46 controls (CG). An ecological momentary assessment (EMA) was used to assess mindfulness, stress, sAA and sCort at six measurements per day on two days each before and after the MBI. Multilevel‐modeling was used to analyze the data on a moment‐to‐moment and averaged day‐level. The IG showed decreased sAA levels (AUCg) from pre to post, while the CG showed increases. Furthermore, diurnal decreases in sCort (AUCi) were pronounced in the IG compared to the CG. On a momentary basis, mindfulness was associated with lower stress and sAA levels, but not sCort. As such, we show that MBI can reduce sympathetic and to a lesser extent hypothalamic‐pituitary‐adrenal activation in daily life. Increased mindfulness can momentarily decrease stress and stress‐related autonomic activation with implications for health. Our results emphasize the importance of brief interventions that can be easily integrated into everyday life. Impact Statement: Our findings add a new perspective on the effects of mindfulness‐based interventions in everyday life: it reduced sympathetic activation reflected in the reduction of saliva alpha‐amylase concentration post intervention. In particular, our results indicate an association between increased mindfulness and reduced perceived stress and saliva alpha amylase on the momentary level. In light of this, brief interventions, that can easily be integrated into everyday life, take on a new significance for psychobiological‐based intervention and evaluation research.